Periprosthetic osteolysis after AES total ankle replacement: Conventional radiography versus CT-scan. Issue 3 (September 2015) - Viste, Anthony; AL Zahrani, Nader; Brito, Nuno; Lienhart, Christophe; Fessy, Michel Henri; Besse, Jean-Luc
Abstract Background The aim of this study was to compare conventional X-rays and CT-scan in detecting peri-prosthetic osteolytic lesions, a major concern after total ankle replacement (TAR). Methods We prospectively assessed 50 patients (mean age 56 years), consecutively operated on by the same senior surgeon, between 2003 and 2006 and with a mean follow-up period of 4 years (range, 2–6.2). The component used was AES® total ankle replacement. The etiologies for total ankle arthroplasty were: posttraumatic in 50%, osteoarthritis secondary to instability in 36%. Plain radiographs were analyzed by 4 independent observers, using a 10-zone protocol (location) and 5 size categories. Results At 4-year follow-up, all patients had been CT-scan assessed with the same protocol by 2 independent observers. Plain radiographs showed dramatic progression of severe periprosthetic lyses (>10 mm): from 14% to 36% of interface cysts for the tibial component respectively at 2 and 4-year follow-up and from 4% to 30% for the talar implant. The talar component was more accurately assessed by CT-scan (mean frontal and sagittal talar lesion: from 270 mm2 to 288 mm2 for CT-scan versus 133 mm2 to 174 mm2 for X-rays). For tibial cysts, axial views showed larger lesions (313 mm2) than frontal (194 mm2) or sagittal (213.5 mm2) views. At 4-year follow-up, 24% of patients had revision with curetage or arthrodesis, and at 7 years follow-up 38% were revised. Conclusion These results are similar to recent AES series, justifying withdrawal of this device. CT-scan was more accurate than X-rays for detecting and quantifying periprosthetic osteolysis. We recommend a yearly radiological control and CT-scan in case of lesion on X-rays.